Ratio between estimated glomerular filtration rates of creatinine and cystatin C predicts overall survival in patients with hepatocellular carcinoma. Issue 2 (12th August 2018) - Tamai, Yasuyuki; Iwasa, Motoh; Kawasaki, Yuya; Yoshizawa, Naohiko; Ogura, Suguru; Sugimoto, Ryosuke; Eguchi, Akiko; Yamamoto, Norihiko; Sugimoto, Kazushi; Hasegawa, Hiroshi; Takei, Yoshiyuki
Abstract : Aim: Hepatocellular carcinoma (HCC) patients with sarcopenia have a poor survival, but there are no predictive markers for survival relating to muscle mass and liver function. Therefore, we investigated whether the ratio between estimated glomerular filtration rates of serum creatinine (Scre) and serum cystatin C (Scys) (eGFRcre/eGFRcys) can be used as a predictive marker of survival in HCC patients. Methods: First, the correlation between Scre/Scys ratio and muscle mass was examined in 50 patients with chronic liver disease. Second, a change in Scre/Scys ratio relating to liver function was investigated in cirrhotic rats. Finally, the relationship between the eGFRcre/eGFRcys ratio and survival was assessed in 86 HCC patients. Results: The Scre/Scys ratio was correlated with skeletal muscle mass index (r = 0.331, P = 0.019) and psoas muscle area index (r = 0.397, P = 0.004) in chronic liver disease patients. In cirrhotic rats, Scre and Scre/Scys ratio were decreased corresponding with liver function. Thirty‐five of 86 HCC patients died within the average follow‐up period of 35 months. The patients with an eGFRcre/eGFRcys ratio <1.26 had significantly longer rates of survival compared to patients with an eGFRcre/eGFRcys ratio ≥1.26 (28.8 vs. 18.5 months, P = 0.001). Using multivariate Cox regression analyses, the patient‐related eGFRcre/eGFRcys ratio (hazard ratio [HR], 4.178; P = 0.007), as well as the tumor‐related factors α‐fetoprotein (HR, 1.000; P < 0.001) and Barcelona Clinic Liver Cancer stage (HR, 2.589; P < 0.001), were independent predictors of survival. Conclusion: The Scre/Scys ratio is associated with muscle mass and liver function. Furthermore, the eGFRcre/eGFRcys ratio could serve as a useful predictive marker for survival of HCC.